Feeding Value of Low and High Protein Dried Distillers Grains and Corn Gluten Meal for Layer - B Tangendjaja; E Wina (Media Peternakan, 2011)
A feeding trial has been conducted to compare feeding value of low and high protein dried distillers grains with solubles (DDGS), and corn gluten meal (CGM) to brown layer in the tropics. Both types of DDGS was included at level 0%, 4%, 8%, 12%, and 16% in the diet while CGM was included at 0%, 2%, 4%, 6%, and 8% in similar content of metabolizable energy (ME) value (2650 kcal/kg) and protein (17%). Each dietary treatment was fed to 4 birds in individual wire cage and replicated 5 times. The trial was performed for 10 weeks and egg production, egg weight, feed intake was measured. At the end of feeding period, manure was collected and analyzed for moisture content while samples of eggs were measured for yolk color and the yolk was analyzed for xanthophyll level. Result showed that feeding Lopro DDGS, Hipro DDGS, and CGM did not affect egg production (egg mass, egg number, and egg weight), however, feeding DDGS resulted in less feed intake (111 g/day) compared to  feeding CGM (114 g/day). Feeding DDGS up to 16% did not affect egg production and similar to feeding CGM up to 8%. Feeding high level of DDGS or CGM did not significantly affect the moisture content of excreta which were between 78.1%-81.9%. Increasing levels of DDGS or CGM increased yolk color score related to the higher level of xanthophylls content in egg yolk. The coloring ability of CGM to egg yolk was higher than that of DDGS. In conclusion, DDGS can be fed to layer up to 16% without affecting egg production while CGM can be fed up to 8% in the diet. DDGS can be used as source of yellow pigment for egg yolk as also found in CGM.